2020
DOI: 10.5194/gmd-13-3179-2020
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of three new surface irrigation parameterizations in the WRF-ARW v3.8.1 model: the Po Valley (Italy) case study

Abstract: Abstract. Irrigation is a method of land management that can affect the local climate. Recent literature shows that it affects mostly the near-surface variables and it is associated with an irrigation cooling effect. However, there is no common parameterization that also accounts for a realistic water amount, and this factor could ascribe one cause to the different impacts found in previous studies. This work aims to introduce three new surface irrigation parameterizations within the WRF-ARW model (v3.8.1) tha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 55 publications
(112 reference statements)
0
36
1
Order By: Relevance
“…Irrigation schemes have already existed in the official WRF model version 4.2 and above (Valmassoi et al, 2020a). We adopted the official irrigation schemes to carry out the relevant experiments and found that the schemes had some shortcomings.…”
Section: Irrigation Schemementioning
confidence: 99%
“…Irrigation schemes have already existed in the official WRF model version 4.2 and above (Valmassoi et al, 2020a). We adopted the official irrigation schemes to carry out the relevant experiments and found that the schemes had some shortcomings.…”
Section: Irrigation Schemementioning
confidence: 99%
“…We implemented drip and channel irrigation schemes in WRF model based on the method described in Valmassoi et al (2020) for the 2000-2018 period. As irrigation method definition differs based on the specific area of implementation, we used the efficiency component, that is, water loss occurred during the application of irrigation.…”
Section: Regional Climate Model Simulationsmentioning
confidence: 99%
“…The drip irrigation scheme here accounts for evaporation only from the soil, which is applied in the chosen LSM. The irrigation water is supplied in the surface rain variable, limiting the direct modulation in the atmospheric and vegetation parameterizations (Lawston et al, 2015;Valmassoi et al, 2020).…”
Section: Regional Climate Model Simulationsmentioning
confidence: 99%
See 2 more Smart Citations